Propuesta de mejora en el proceso de tintura de fibras textiles en poliamida (2019)
With the proposal for improvement and from the technical evaluation of the dyes and dye auxiliaries proposed (optical bleach, equalizer, acid donor, fixative, detergent, yellow, blue, bright yellow, bright red and black dyes) the decrease was achieved. chemical cost of the dyeing process and of the bleaching process of polyamide fibers by 56.16% and 4.12% respectively, where not only the quality of the final product was ensured so that uneven dyeing, dizziness or scratching is not present, but that the solidity tests governed by the American Association of Textile Chemists and Dyes (AATCC) were improved where the results of the tests of solidity to washing, exposure to sea water and chlorinated pool water and rub solidity they were improved and they were able to comply with ranges established by Priotela S.A. which must be greater than or equal to 3.5.